2023
DOI: 10.1177/00332941231183614
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Capital, Autonomous Motivation and Innovative Behavior: A Study Aimed at Employees in Social Networks

Carlos Blasco-Giner,
Adalgisa Battistelli,
Isabella Meneghel
et al.

Abstract: The present study investigates the relationship between positive psychological capital (PsyCap) and innovative work behavior (IWB), as mediated by autonomous motivation and participative leadership moderation. The study was conducted on a sample of 246 employees from various public and private organizations, recruited through different social networks. The moderated mediation analysis provided evidence about the impact of employees’ PsyCap on their innovative behavior at work. This behavior will be higher when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 103 publications
2
3
0
Order By: Relevance
“…These findings reveal a noteworthy positive correlation between intrinsic learning motivation and learning outcomes, aligning with prior research (Fredricks and McColskey, 2012;Lazowski and Hulleman, 2016). Similarly, the observed positive impact of emotional engagement on college students' learning outcomes is consistent with earlier conclusions from research (Raver, 2002;Bierman et al, 2008;Liew et al, 2008;Engels et al, 2021;Hasnine et al, 2023). In the blended learning environment, the psychological capital of college students has a significant impact on the learning effect of college students, which is in alignment with previous research conclusions (Jafri, 2013).…”
Section: Discussion and Suggestionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings reveal a noteworthy positive correlation between intrinsic learning motivation and learning outcomes, aligning with prior research (Fredricks and McColskey, 2012;Lazowski and Hulleman, 2016). Similarly, the observed positive impact of emotional engagement on college students' learning outcomes is consistent with earlier conclusions from research (Raver, 2002;Bierman et al, 2008;Liew et al, 2008;Engels et al, 2021;Hasnine et al, 2023). In the blended learning environment, the psychological capital of college students has a significant impact on the learning effect of college students, which is in alignment with previous research conclusions (Jafri, 2013).…”
Section: Discussion and Suggestionsupporting
confidence: 90%
“…Previous studies have found motivation as a mediator. For example, Autonomous motivation mediates the relationship between individual psychological capital and innovative work behavior (Blasco-Giner et al, 2023). Intrinsic motivation was measured as a significant mediator between psychological capital and study engagement (Siu et al, 2014).…”
Section: Discussion and Suggestionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced self-efficacy contributes to a belief in one's capabilities, fostering a proactive and motivated approach to tasks. Optimism cultivates a positive outlook, encouraging employees to approach challenges enthusiastically rather than Furthermore, the findings also confirmed a positive effect of PC and EM, which is supported by domain studies (Çavuş and Gökçen, 2015;Schuckert et al, 2018;Simons and Buitendach, 2013;Siu et al, 2014;Blasco-Giner et al, 2023). These results reflect that higher self-efficacy, optimism, resilience, and hope within the PC framework create a conducive atmosphere for motivated behaviour.…”
Section: Structural Modelsupporting
confidence: 65%